Fuzzy cozy / Nur Syakirin Rosmizam - Rosmizam, Nur Syakirin (Universiti Teknologi MARA, Kedah, 2025)
The objective of this study is to rebrand the "The Cat Who Bakes" bakery. Situated in Damansara Damai, Petaling Joya, Selangor, this bakery is quaint and distinc tive. Founded in 2020, this welcoming space blends the comforts of freshly made bread, delicious sweets, and fragrant coffee with the entertaining company of cats. In the company of friendly feline residents, the bakery's cat-themed atmosphere creates a cosy, welcoming area where patrons can unwind and savour their delights. However. few major weaknesses have been found, such as the lack of consistency in logo elements, inconsistency of logo usage, and no implementation of the concept in the advertising. Thus, a new name came alive which is Fuzzy Cory Bakery. The Fuzzy Cory Bakery is a warm and inviting establishment that offers a unique blend of freshly baked goods and a charming cat-themed ambiance. The name "Fuzzy" symbolises the soft, comforting fur of cats, while "Cozy'' reflects the welcoming, homely atmosphere the bakery embodies. The thoughtfully designed logo, incorporating elements of both cats and bread, effectively conveys the bakery's distinctive concept Guided by the tagline. "Every bite makes you purr," Fuzzy Cozy Bakery is dedicated to delivering a delightful culinary experience where customers can savour delicious treats while enjoying the company of adorable companions. Whether it's freshly baked bread. decadent pastries, or a warm cup of coffee, Fuzzy Cozy Bakery's vast and wellchosen menu offers patrons a range of alternatives to satisfy their cravings. The bakery is the perfect spot to unwind and recharge because of its well-thought-out interior design, which features warm, inviting colours and comfortable accents that foster a peaceful atmosphere. In addition to offering mouthwatering delights, Fuzzy Cozy Bakery is a sanctuary where customers may find calm, escape the stress of everyday life, and relish happy, cosy limes. It's more than just a bakery; it's a destination for comfort, flavour, and joy .